(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The effectiveness of management of the state economy is directly linked to performance management of economic activities of its regions. The economic and social effectiveness of each branch depends on the extent to which effectively formed and valid a management system of the economic complex and its components in the region is.